International Trade Dynamics of Islamic Countries: An Analysis of Challenges and Opportunities Amid Global Economic Flows - Sugianto, Aan; Fadli, Royyan (International Journal of Islamic Business and Management Review, 2025)
This study aims to analyze the challenges and opportunities of international trade of Islamic countries in the midst of global economic flows using a descriptive qualitative approach based on literature studies. Data was obtained from reports from international institutions such as the World Bank, IMF, OECD, and IsDB, as well as academic literature related to Islamic economics and international trade. The analysis was carried out through the integration of conventional trade theory, competitive advantage theory, and Islamic value approach based on the concepts of Maqāṣid al-Sharī'ah and Value-Based Intermediation (VBI). The results of the study show that the main challenges of international trade of Islamic countries include economic structural inequality, non-tariff barriers, fragmentation of halal standards, technological gaps, as well as delays in facing digitalization and green economy. However, great opportunities also open up through strengthening the digital economy, transitioning to green trade, Islamic finance innovation, and collaboration between OIC countries in building value-based trading systems. The integration of Maqāṣid al-Sharī'ah and VBI can be a strategic basis for Islamic countries to create a competitive, fair, and sustainable trading system. This research confirms that the success of the Islamic world in dealing with economic globalization is determined not only by structural reforms, but also by the ability to internalize Islamic values in international trade policies and practices. Thus, international trade between Islamic countries has the potential to become a new moral and economic force that is able to encourage the creation of a more balanced, inclusive, and civilized global economic order.